Improving Students’t Reading Comperhension of Descriptive Text By Using Preview, Question, Read, State, and Test (PQRST) for Seventh Grade of SMPN 38 Palembang - Aprilia Arista; Nike Angraini; Badriyah Ulfah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Teaching reading was something that was challenging for teachers because not all students can understand what they read. This study aimed at answering the problems of how the PQRST technique improved students’ understanding in reading descriptive text. Then, the technique used to improve reading comprehension achievement in descriptive text was the PQRST method by using this method students were trained to understand the contents of descriptive text during 12 meetings. The sample of this study consisted of 33 students as control group of 34 students as experimental group. The data collection techniques used in this study were pre-test and post-test. Data analysis used t-test (paired sample t-test and independent sample t-test). The results of the paired sample t test in the experimental group showed that the obtained t was 13,552 t-table (df=23) was 2,068 at a significance of 0.05. This means that there was a significant improvement in students’ reading comprehension achievement after being taught using the PQRST method. Furthermore, the result of independent sample t-test showed that the t obtained was 7.975 > t-table (df=47) was 2.011 at a significance of 0.05. This means that there was a significant mean difference between the experimental and control groups. Also, there was significant mean difference beetwen the students who were taught by using PQRST and those who were not. The results of the study that improved the action hypothesis was accepted. By using the PQRST method, the reading comprehension achievement of grade VII students of SMPN 38 Palembang in the 2021/2022 academic year improved.